PENILAIAN RISIKO KECELAKAAN KERJA PADA PENGGUNA SCAFFOLDING DI PROYEK PEMBANGUNAN HOTEL GATOT SUBROTO MEDAN TAHUN 2012 - Dewi Juliatin; Lina Tarigan; Eka Lestari (Lingkungan dan Kesehatan Kerja, 2013)
Occupational accident risk assessment on scaffolding users at Gatot Subroto Hotel construction project in 2012. Gatot Subroto Hotel Construction Project built to 12 floors using 24 scaffolding with high 40,8 meters. Scaffolding condition not suitable used and workers don’t use personal protective equipment. This study purposed to assess the risk of occupational accident to scaffolding users at Gatot Subroto Hotel construction project. The descriptive study population was 26 workers, sampling based on purposive sampling technique, complete the requirements have used scaffolding, put in brick, roughcast and softcast, worked on 14 – 20 May 2012 and ready to interview, the sample was 17 workers. Occupational accident risk assessment done by form R = P x C, when put in brick, roughcast and softcast. The results obtained the highest risk working scaffolding on putting in brick with 11 risks, roughcasting with 10 risks and softcasting with 9 risks. By accounting mean for each probability, consequences and level of risk obtained probability on putting in brick at score 4 (very likely),on roughcasting at score 3 (likely) and on softcasting at score 3 (likely). Consequences on putting in brick at score 3 (moderate), on roughcasting at score 3 (moderate) and on softcasting at score 3 (moderate). Risk assessment on putting in brick at moderate risk, on roughcasting at moderate risk and on softcasting at moderate risk. Based on the results suggested to use main frame suitable used, platform made from iron or metal, mix materials in the pail or building, give training to workers haven’t skilled yet and personal protective equipment. Key words : scaffolding user, risk assessment, probability, consequences